2017
DOI: 10.3390/ijms18091989
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Attenuates Manganese-Induced Neuroinflammation by Alleviating Oxidative Stress through Regulation of Apoptosis, iNOS/NF-κB and HO-1/Nrf2 Pathways

Abstract: Manganese (Mn) is an essential trace element required for the development of human body and acts as an enzyme co-factor or activator for various reactions of metabolism. While essential in trace amounts, excessive Mn exposure can result in toxic accumulations in human brain tissue and resulting extrapyramidal symptoms called manganism similar to idiopathic Parkinson’s disease (PD). Quercetin (QCT) has been demonstrated to play an important role in altering the progression of neurodegenerative diseases by prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 54 publications
2
70
0
Order By: Relevance
“…Previous studies have shown that Mn caused generation of reactive oxygen species (ROS). 23 Rap did not alter generation of ROS, suggesting that mTORC is a target downstream of ROS. Indeed, ROS caused activation of mTORC, which contributed to induction of the IRE1 pathway, but not the PERK and ATF6 pathways.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies have shown that Mn caused generation of reactive oxygen species (ROS). 23 Rap did not alter generation of ROS, suggesting that mTORC is a target downstream of ROS. Indeed, ROS caused activation of mTORC, which contributed to induction of the IRE1 pathway, but not the PERK and ATF6 pathways.…”
Section: Discussionmentioning
confidence: 87%
“…The results showed that Rap pretreatment significantly activated autophagy and IRE1 signaling pathway, as well as partially decreased α‐Syn oligomers. Previous studies have shown that Mn caused generation of reactive oxygen species (ROS) . Rap did not alter generation of ROS, suggesting that mTORC is a target downstream of ROS.…”
Section: Discussionmentioning
confidence: 96%
“…As found in macrophages, quercetin activated the Kelch-like ECH-associated protein-1(Keap1)-Nrf2 signaling pathway to induce HO-1 expression for protection against oxidative stress and inflammatory responses [10]. Quercetin could effectively inhibit manganese-induced oxidative stress and inflammatory response in neuraltumor epithelialcells (SK-N-MC) in Sprague-Dawley rats though activating HO-1/Nrf2 and inhibiting the NF-κB pathway [31]. Additionally, quercetin could improve mitochondrial function by promoting the translocation of Nrf2 from the cytoplasm to the nucleus and activating the Nrf2 signaling pathway [32,33].…”
Section: Discussionmentioning
confidence: 96%
“…3–3′ diaminobenzidine (DAB) was used as a chromogen. Staining of the background was performed using hematoxylin …”
Section: Methodsmentioning
confidence: 99%